The causal relationship between government investment and economic development in ASEAN countries - Nhung, Vu Cam; Ven, Luu Phuoc (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this article is to evaluate the impact of public investment on economic growth. The data was used from the annual data of the Asian Development Bank (ADB) for 6 countries in ASEAN during 2000-2022. The methodology used in the project is to apply the unit root test to the stationarity properties of individual time series and establish the cointegration relationship between non-stationary variables using methods related to cointegration testing in the long-run. The error correction model (ECM) considers the impact of the variables public investment, public expenditure and budget revenue from taxes on short-term economic growth and long-term growth thereby calculating the adjustment speed and adjustment time of the model and using the Granger causality test with fixed effects for analysis of unbalanced panel data to comprehensively analyze the relationship between public investment and economic growth. Data analysis and processing were performed using Stata software version 17. The findings that public investment has a long-term impact on economic growth and has a two-way causal relationship in all countries. The authors provide policy implications to make public investment more effective contributing to promoting the country's socio-economic development, reviewing and improving the legal system on public investment, restructuring public investment while strongly enhancing the efficiency and quality of public investment, inviting and attracting foreign direct investment (FDI) capital, diversifying capital sources and creating more motivation for the private economic sector to develop and promulgate solutions to develop high-quality human resources.